Kontribusi Kelengkapan Media Pembelajaran, Manajemen Kelas, dan Motivasi Berprestasi Terhadap Hasil Belajar Mata Pelajaran Peminatan Kejuruan Pada Siswa Kelas XI Jurusan Perhotelan - D.M.W. Sari; I.M. Yudana; D.G.H. Divayana (Jurnal Administrasi Pendidikan Indonesia, 2021)
This study aims to determine the contribution of the completeness of learning media, class management, and achievement motivation to the learning outcomes of Vocational Specialization subjects in class XI students of Hospitality Department at SMK Negeri 1 Sukasada. The population in the study was 140 students. A sample of 103 students was obtained by random sampling technique. Data on the completeness of instructional media, class management, and achievement motivation were collected by means of a questionnaire and data on learning outcomes were collected by studying documents on student learning outcomes in the schools. Data analysis used simple regression analysis, multiple regression, and partial correlation. Based on the research data analysis, the results show that: 1) there is a significant contribution of the completeness of learning media to the learning outcomes of vocational specialization subjects in class XI students majoring in hospitality at SMK Negeri 1 Sukasada, with a contribution of 37.9% and an effective contribution of 14.39 %, 2) there is a significant contribution of class management to the learning outcomes of vocational specialization subjects in class XI students majoring in hospitality at SMK Negeri 1 Sukasada, with a contribution of 54.5% and an effective contribution of 23.32%, 3) there is a significant contribution significant achievement motivation on learning outcomes of vocational specialization subjects in class XI students majoring in hospitality at SMK Negeri 1 Sukasada, with a contribution of 54.9% and an effective contribution of 24.86%, and 4) there is a simultaneous significant contribution to the completeness of learning media , class management, and achievement motivation on learning outcomes in Pe Vocational interest in class XI students majoring in hospitality at SMK Negeri 1 Sukasada, with a contribution of 62.6%.